Assessing Critical Care Nurse’s Knowledge and Adherence to Evidence-Base Guidelines for Ventilator-Associated Pneumonia Prevention in Palestinian Hospitals - Ismael Ahmad Al-Nawaja’a; Basma Salameh; Dalia Toqan; Bahaaeddin M. Hammad; Imad Fashafsheh (Nursing Research and Practice)
Conclusion: Critical care nurses possess an average level of knowledge regarding EBGs for preventing VAP, alongside demonstrating an acceptable level of adherence to these guidelines.